Four Surgical Modifications to the Classic Elastase Perfusion Aneurysm Model Enable Haemodynamic Alterations and Extended Elastase Perfusion. (July 2018) - Busch, Albert; Chernogubova, Ekaterina; Jin, Hong; Meurer, Felix; Eckstein, Hans-Henning; Kim, Mia; Maegdefessel, Lars
Abstract : Objective/Background: Abdominal aortic aneurysm (AAA) is an individual and socioeconomic burden in today's ageing society. Treatment relies on surgical exclusion of the dilated aorta by open or endovascular repair. For research purposes, animal models are necessary and the elastase induced aneurysm model closely mimics end stage human aneurysm disease. To improve the translational value of this model, four modifications to the classic elastase perfusion procedure (PPE) in relation to human aneurysm morphology were conducted. Methods: In ten week old male C57BL/6J wild type mice the PPE procedure was modified in four ways using two different techniques. Flow alteration was simulated by partial ligation of the common iliac artery or the distal aorta. Additionally, careful exploration of the abdominal aortic branches allowed PPE induction at the suprarenal and iliac level. Molecular biology, ultrasound, and immunohistochemistry were used to evaluate these pilot results. Results: Two aortic outflow obstructions simulating distal aortic or iliac stenosis significantly increase murine AAA diameter ( p = .046), and affect local vascular wall remodelling. Suprarenal aortic dissection allows a juxtarenal aneurysm to be induced, similar to the angiotensin II induced aneurysm model. A separate investigation for canonical activation of transforming growth factor β in the two embryonically distinct juxtarenal and infrarenal segments showed no distinct difference. Creating an aortoiliac bifurcated aneurysm completes the mimicry of human aneurysm morphology. Conclusion: The alteration of the classic PPE aneurysm by outflow modulation and further elastase perfusion to the juxtarenal and aortoiliac segment modifies morphology and diameter, and thus increases the translational value in future research.